The singular insemination status of Hypothenemus hampei (Ferrari) (Coleoptera: Curculionidae: Scolytinae) females during the inter-harvest season of a coffee crop. Issue 4 (5th December 2018) - Román-Ruiz, A.K.; Barrera, J.F.; Cruz-López, L.; Rojas, J.C.; Dufour, B.P.
Abstract: The coffee berry borer, Hypothenemus hampei (Ferrari), can survive in residual coffee berries during the inter-harvest period, while new fructification only appears 2–3 months after the last harvest. The dispersal of colonizing females is an adaptation that enables the life cycle of the species to go ahead whenever his flight aptitude allows. This paper focuses on accurately determining the rate of inseminated females ready to reproduce when emerging from residuals berries to colonize new ones, which constitutes a characteristic of the live cycle far from common in Curculionidae. We dissected females caught in traps baited with a mixture of alcohols during the inter-harvest season, females from infested residual berries collected from branches, and virgin females obtained from pupae reared individually in the laboratory. After microscopic preparation with Giemsa stain, spermathecae were observed to identify the physiological status of each specimen. Out of the females found in the traps, 98.4% displayed recent and abundant insemination and 1.6% sporadic insemination. In contrast, in residual berries, most of females were recently inseminated (84.5%), followed by virgin females (10.5%) and older inseminated females (5%). In addition, the flight tests of the virgin females were negative. These results indicate that all colonizing females were inseminated, ready for flying and oviposition, females inside residual berries showed different physiological status, and virgin females could not migrate since they could not flight. The large number of inseminated females inside the residual berries, and the capacity of migrating females to colonize and reproduce, suggest that it is necessary to control residual berries and use traps to stop the dispersal and reproduction of this pest.